Fabrication of micofluidic device for blood separation - Choo, Hui Huang (2015)
Blood plasma is an important assay for many diagnostic tests typically performed in clinical laboratories to identify the specific molecules, the biomarkers, in the assay, which may reflect the current status of pathological processes in the human body. The typical method for separating the plasma from red blood cells (RBCs) in whole blood (WB) is by centrifuge. Like other complex blood separation technologies, the centrifugation method requires proper laboratory infrastructure in centralized hospital laboratories, hence it does not provide rapid results for point-of-care diagnostics. There is an urgent need for devices, which provide rapidly on site separation of plasma from whole blood for use in uncomplicated and swift point-of-care (POC) diagnostics for infectious diseases or cancerous diseases, and also for the storage stability of the components in the blood. Microfluidics approaches can be used for on-chip plasma isolation from WB via suitable driving or separation mechanisms such as capillary force or Zweifach–Fung effect. These approaches possess some drawbacks such as the need for achieving necessary flow speed with microfluidic pump that makes them unsuitable for POC testing. In this project, a lab-on-a-chip microfluidic device capable of separating plasma from the whole blood for blood sample preparation is presented. This microfluidic device does not require the use of complicated microfluidic pumps and is capable to handle small blood sample volume. It is capable to pull red blood cells away from whole blood. The low cost microfluidic device will not only be portable and practical, it gives faster results as compared to several conventional methods and can be utilized under resource-constrained settings. The results obtained in this project will be served as stepping-stone towards the development of a convenient and disposable point-of-care technology for use in hospitals, clinics and most importantly resource constrained facilities.